Acute haemodynamic benefits of biatrial atrioventricular sequential pacing: comparison with single atrial atrioventricular sequential pacing. (12th March 2004) - Doi, A; Takagi, M; Toda, I; Yoshiyama, M; Takeuchi, K; Yoshikawa, J
Abstract : Objective: To evaluate the acute effects on haemodynamic variables of biatrial pacing in comparison with high right atrial (HRA) pacing and left lateral atrial pacing. Patients and design: 23 patients were paced from the HRA site, the lateral site of the coronary sinus (CS), and both sites on two fixed atrioventricular delays (100 and 150 ms) during atrioventricular sequential pacing at 80 and 100 beats/min in random order. Main outcome measures: After five minute pacing, the maximum P wave duration on a 12 lead ECG, cardiac output, pulmonary capillary wedge pressure, and the transmitral flow pattern by transthoracic echocardiography were measured. Results: Biatrial pacing delivered the shortest P wave duration (133 (25) ms, 133 (27) ms, and 96 (15) ms during HRA, CS, and biatrial pacing, respectively; p < 0.001), and the most improvement in cardiac output and pulmonary capillary wedge pressure (3.71 (0.93) l/min and 15 (7) mm Hg, 3.79 (0.97) l/min, and 14 (6) mm Hg, and 4.09 (1.01) l/min and 13(6) mm Hg during HRA, CS, and biatrial pacing, respectively; p < 0.01). Biatrial pacing most significantly decreased the intervals between the atrial pacing spike and the peak and end of the atrial filling wave (186 (16) ms and 250 (22) ms, 172 (19) ms and 242 (24) ms, and 153 (15) ms and 227 (23) ms during HRA, CS, and biatrial pacing, respectively; p < 0.001). It also significantly increased the mitral flow time velocity integral and peak atrial filling wave velocity (7.5 (3.4) cm and 63.8 (17.6) cm/s, 7.8 (3.0) cm and 62.4 (16.6) cm/s, and 8.3 (3.4) cm and 67.8 (19.3) cm/s during HRA, CS, and biatrial pacing, respectively; p < 0.05). The improvements in haemodynamic variables were especially remarkable in patients who had a longer interatrial conduction delay. Conclusions: Biatrial pacing yielded the most significant improvements in haemodynamic variables. These haemodynamic benefits may play a part in reducing intra-atrial pressure and preventing atrial fibrillation.